RELATIONSHIP BETWEEN GREEN BONDS AND OTHER FINANCIAL ASSETS: A BIBLIOMETRIC ANALYSIS - Herlina, Herlina; Dewayanto, Totok (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract - Green bonds have evolved in line with the aspirations of the economy. Green bonds, an initiative of economies to innovate and sustainably transform their financial systems, have drawn the attention of academics and policymakers due to the growing global concern for environmental protection, climate change mitigation, and adaptation. The purpose of this study is to investigate the development and scholarly evolution of the Green Bond idea through bibliometric analysis. A survey of academic literature from 2016 to 2024 (May) was conducted using the Scopus database. Intellectual structure and bibliographic analysis of the selected articles were conducted using R-Packages software and WebInterface Biblioshiny. The journals used in this study are Scopus-indexed journals, which are searched using the keywords green bond, cointegration, transmission, and spillover. The results showed that the theme of green bonds is exciting to research because it has increased yearly. France became the most researched country and produced 24 frequencies of articles. The most productive country with the most citations is China, which has 663 citations. Previous studies have found a spillover transmission from the financial asset market to the green bond market. This suggests that volatility in financial markets will spill over and affect the green bond market. This research can be used as an investment decision-making strategy, especially in building an investment portfolio. Keywords: Bibliometrix; Green Bond; Green Finance; Scopus; Spillover.